Psychotropic Medications Are Associated With Increased Liver Disease Severity in Pediatric Nonalcoholic Fatty Liver Disease. Issue 3 (September 2019) - Mouzaki, Marialena; Yodoshi, Toshifumi; Arce-Clachar, Ana C.; Bramlage, Kristin; Fei, Lin; Ley, Sanita L.; Xanthakos, Stavra A.
ABSTRACT: Objectives: The aim of the study was to determine whether pediatric patients with nonalcoholic fatty liver disease (NAFLD) exposed to psychotropic medications have more severe liver disease compared to their counterparts who are not on these medications. We hypothesize that use of psychotropic agents is associated with liver disease severity. Methods: Children and adolescents with biopsy-confirmed NAFLD were included in this study. Histology data, detailed clinical information, and results of serum biochemistries performed within 3 months of the liver biopsy were collected retrospectively. Univariate and multivariate modeling was used to determine differences between the groups and to control for confounders. Results: A total of 228 patients were included, 17 (8%) of whom where on psychotropic medications at the time of the liver biopsy. Patients on psychotropic medications were more likely to also be on metformin (53% vs 18%, P < 0.01) and antihypertensive medications (29% vs 8%, P < 0.01) compared to children with NAFLD who were not on psychotropic agents. There were no differences in regards to biochemical evidence of liver injury, insulin resistance, and dyslipidemia between the groups. On histology, however, the use of psychotropic medications was associated with increased steatosis severity (score 2.4 vs 1.9, P = 0.04) and increased likelihood of having an NAFLD Activity Score ≥5 (seen in 59% vs 35% or patients; P = 0.05, respectively). Conclusions: In this large cohort of children with biopsy-confirmed NAFLD, the use of psychotropic medications was associated with increased liver disease severity. Exposure to psychotropic agents should be considered when risk stratifying children with NAFLD. Abstract : Supplemental Digital Content is available in the text